Intimate rivals : Japanese domestic politics and a rising China - Smith, Sheila A., 1959- (Council on Foreign Relations Book., 2015)
No country feels China's rise more deeply than Japan. Through intricate case studies of visits by politicians to the Yasukuni Shrine, conflicts at the East China Sea boundary, concerns about food safety, and strategies of island defense, Sheila A. Smith explores the policy issues testing the Japanese government as it tries to navigate its relationship with an advancing China. She finds that Japan's interactions with China extend far beyond the negotiations between diplomats to include a broad array of social actors intent on influencing the Sino-Japanese relationship. Some of the tensions com.